Facebook Sebagai Komunikasi yang Dimediasi Komputer - Natalia Widiasari (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
Computer-Mediated Communication (CMC) is a concept that is still relevant and applicable today. The theory discusses and captures most of the phenomenas and problems on online communication along with its potentiality to develop. Facebook as one of the oldest social media that is still growing in the term of user number and extensively used world wide is another phenomenon itself. Discussion about application of CMC concepts in Facebook reveals some of conceptual limitation. CMC discussion is lacked of leadership, even though user could participate equally. The participation at some degree is silenced by self- censorship. While the features of CMC are developed, face-to-face communications remains the best of all. This article is based on literature study where secondary data is used to build the argument.